Exploring the Relationship Between Need for Closure, Religious Ideology, and Identity Fusion - Istiqomah, Istiqomah; Sombuling, Agnis; Umam, Ahmad Naufalul (Psikis : Jurnal Psikologi Islami, 2025)
This study examines how the need for certainty drives individuals to form strong bonds with religious groups, a process known as identity fusion. We explore whether epistemic needs—motivations for clarity, assessed by the need for closure—encourage identity fusion indirectly by fostering religious ideology - a shared system of beliefs that reduces uncertainty and strengthens group identity. Grounded in uncertainty reduction theory and motivated reasoning, we hypothesized that while uncertainty alone does not directly predict identity fusion, it indirectly strengthens fusion through religious beliefs. Using cross sectional design from survey data of 580 Indonesian participants aged 17 to 46, we assessed relationships among need for closure, religious ideology, and identity fusion. The instruments included the Indonesian-adapted Need for Closure Scale (α = .79), the Religious Ideology Subscale (α = .79), and pictorial measures of identity fusion. Mediation analysis confirmed that need for closure predicts identity fusion through religious ideology measurement, which fully mediates this relationship. Findings suggest that those seeking certainty are more likely to embrace religious ideologies, thereby intensifying their group bond. This research highlights how ideologies serve as frameworks that help individuals manage uncertainty, enhancing their identity with the group. These insights contribute to understanding the role of epistemic motivations in identity formation and may inform strategies to address group conflict. Future directions include investigating the development of identity fusion over time.